Pengaruh Kualitas dan Diferensiasi Produk Terhadap Loyalitas Pelanggan - Hanyani, Tania; Fadillah, Adil (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
The quality of the product is a combination of the properties of the product in use in accordance with customer’s expectations and goals. While differentiation is the effort of a company to differentiate its products from competitors' products in a trait that makes it more desirable. In consuming the products customers are often confronted by a variety of brands, the company should be able to create a quality product and has the distinction or differentiation in order to increase customer loyalty. The purpose of this study was to determine the quality of products J.CO Donuts & Coffee at the moment. To find product differentiation J.CO Donuts & Coffee at the moment. Determine the effect of product quality J.CO Donuts & Coffee on customer loyalty at this time. Then determine the effect of product differentiation J.CO Donuts & Coffee for the current customer loyalty, and to determine the effect of quality and product differentiation J.CO Donuts & Coffee on customer loyalty at this time. The results showed that the relationship of product quality on customer loyalty is equal to 0.749 and accounts for 56 percent of customer loyalty and product differentiation of the relationship variables on customer loyalty is 0.715 and accounts for 51.1 percent. Analysis of the correlation coefficient on the variable customer loyalty is to have 0.770 showed a strong relationship between the independent factors on customer loyalty, amounting to 77 percent. From this analysis it can be concluded that product quality and product differentiation effect on customer loyalty. This can be evidenced from the contribution of a given variable product quality and product differentiation on customer loyalty. Keywords: Quality Products, Product Differentiation, Customer Loyalty